Investigation of Structure-Property-Boiling Enhancement Mechanisms of Copper/Graphene Nanoplatelets Coatings - Rishi, Aniket M.; Rozati, Seyed Alireza; Trybus, Carole; Kandlikar, Satish G.; Gupta, Anju (Frontiers in Mechanical Engineering, 2021)
In this work, we present an exceptionally high heat transfer coefficient (HTC) and critical heat flux (CHF) achieved by graphene nanoplatelets (GNPs) and copper composite coatings with tunable surface properties. These coatings were created by a combination of powder metallurgy and manufacturing processes including ball milling, sintering, electrodeposition, and salt-patterning. We demonstrated correlations between various coating processes, resultant surface morphologies, properties, and improved boiling mechanism. Electrodeposition of GNP and copper particles led to formation of tall ridge-like structures and valleys to contain the boiling fluid in between. Higher CHF achieved for these coatings was attributed to the microlayer evaporation. It was observed that ball milling of GNP and copper particles prior to their sinter-coating enhanced their surface roughness that resulted in very high HTC, nearly 5.4 times higher than plain copper surfaces. Additional salt-patterning along with sinter-coating yielded interconnected porous networks with high nucleating activity that rendered record-breaking HTC of 1,314°kW/m2-°C. Combination of these coating processes can be adopted to tailor the surfaces and achieve better boiling performance. Novel techniques developed in this work can be applied to a variety of thermal engineering applications.